2023
DOI: 10.3390/fire6080318
|View full text |Cite
|
Sign up to set email alerts
|

Combustion of Liquid Fuels in the Presence of CO2 Hydrate Powder

Abstract: The process of combustion of a liquid fuel layer (diesel, kerosene, gasoline, separated petroleum, and oil) in the presence of CO2 hydrate has been studied. These fuels are widely used in engineering, which explains the great interest in effective methods of extinguishing. Extinguishing liquid fuels is quite a complicated scientific and technical task. It is often necessary to deal with fire extinction during oil spills and at fuel burning in large containers outdoors and in warehouses. Recently, attention to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…On the other hand, for the calculation of mass transfer limitations of a gas-phase reaction inside the chemical reactor (for example, in a fixed bed reactor), a large number of variables needs to be considered in the simulation tests, as can be seen in the paper of García-Sánchez et al [53]. Therefore, after finding the optimal reaction rate for the indene catalytic reaction under chemical reactor conditions, it should then be compared with the observed reaction rate, which may be affected by the external mass diffusion [54] and intrinsic reaction rate of the catalyst species. If a detailed analysis indicates the authors' assumptions presented in "Reaction Step g→h (Temperature Range ∆T~510-620 • C)", only then can it be confirmed that the reaction rate can shows the mass transfer limitation.…”
Section: Modelmentioning
confidence: 99%
“…On the other hand, for the calculation of mass transfer limitations of a gas-phase reaction inside the chemical reactor (for example, in a fixed bed reactor), a large number of variables needs to be considered in the simulation tests, as can be seen in the paper of García-Sánchez et al [53]. Therefore, after finding the optimal reaction rate for the indene catalytic reaction under chemical reactor conditions, it should then be compared with the observed reaction rate, which may be affected by the external mass diffusion [54] and intrinsic reaction rate of the catalyst species. If a detailed analysis indicates the authors' assumptions presented in "Reaction Step g→h (Temperature Range ∆T~510-620 • C)", only then can it be confirmed that the reaction rate can shows the mass transfer limitation.…”
Section: Modelmentioning
confidence: 99%
“…In class A fire experiments, CO 2 hydrates proved exceptional in suppressing wood fires, requiring less mass than water, snow, or ice. 10 Recent work by Misyura et al 16 investigated CO 2 hydrate powder for extinguishing liquid fuels, identifying distinct evaporation modes and showcasing its efficiency in flame suppression, especially with varying flow rates. The findings suggest potential applications using pressed tablets or granules for volumetric fires and porous powders for local combustion with low flame height.…”
Section: Introductionmentioning
confidence: 99%